2011
DOI: 10.1002/fuce.201100098
|View full text |Cite
|
Sign up to set email alerts
|

A H2/O2 Fuel Cell for In situ μ‐Raman Measurements. In‐depth Characterization of an Ionic Liquid Filled Nafion Membrane

Abstract: We report the design of a H2/O2 (fuel) cell for in situ μ‐Raman spectroscopic measurements. The horizontal orientation of the cell is conceived to allow the penetration of the laser beam along the z‐axis from one electrode to the other. We show that during in‐depth analyses the Raman signal is not significantly lost and the axial resolution is sufficiently good to allow quantitative and qualitative spectral interpretation. We report “proof of principle” tests performed on Nafion membranes swelled with protic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…11) and EIS analysis (Fig. 12-14) show that (i) the confinement of the IL in the matrix does not affect its physical properties and (ii) that the conductivities in the IGs are comparable to those observed in other IGs [19,2325 36]. In all cases DSC only finds a glass transition, which is independent both of the matrix type (TBA, TBM, MBA, MBM) and also of the fraction of IL present in the IGs.…”
Section: Discussionmentioning
confidence: 99%
“…11) and EIS analysis (Fig. 12-14) show that (i) the confinement of the IL in the matrix does not affect its physical properties and (ii) that the conductivities in the IGs are comparable to those observed in other IGs [19,2325 36]. In all cases DSC only finds a glass transition, which is independent both of the matrix type (TBA, TBM, MBA, MBM) and also of the fraction of IL present in the IGs.…”
Section: Discussionmentioning
confidence: 99%
“…An emerging application is the in situ measurement of concentration profiles of water diffusing across the membrane thickness . Very recently, a few measurements of water gradients across the membrane operating in the PEMFC have been reported . The aim of these studies is to contribute to the PEMFC water management fundamental understanding and the main requirement is, obviously, to quantitatively measure the water content of the membrane at each point of the depth scan.…”
Section: Introductionmentioning
confidence: 99%
“…A last work has to be mentioned for completeness, even if concerning materials and FC design sensibly far from the state-of-art. Martinelli et al [90] reported ªproof of principleº microspectroscopy measurements with a H 2 /O 2 cell containing a Nafion 117 membrane swollen with protic ionic liquids (PILs). A neat membrane was used and the gas diffusion and active layers were replaced by simple platinum grids, leaving voids for the Raman collection.…”
Section: Resultsmentioning
confidence: 99%